Matched pilot study examining cannabis-based dronabinol for acute pain following traumatic injury. Issue 1 (9th February 2020) - Schneider-Smith, Elisabeth; Salottolo, Kristin; Swartwood, Claire; Melvin, Casey; Madayag, Robert M; Bar-Or, David
Abstract : Background: To determine whether adjunctive dronabinol, a licensed form of delta-9-tetrahydrocannabinol, reduces opioid consumption when used off-label for managing acute pain following traumatic injury. Methods: This matched cohort study included patients who were admitted with a traumatic injury between 1 March 2017 and 30 October 2017. The hospital pharmacy database was used to identify patients who received dronabinol (cases), and they were matched 1:1 to patients who did not receive dronabinol (controls) using age, cause of injury and hospital length of stay. The primary outcome, change in opioid consumption, was calculated using morphine milligram equivalents (MME). The change in MME was calculated for cases as total MME over 48 hours with adjunctive dronabinol minus 48 hours prior to dronabinol, and for controls as total MME 48–96 hours from admission minus 0–48 hours from admission. Data are presented as mean and SE or median and IQR. Statistical analysis was performed using paired t-tests and McNemar's tests. Results: There were 66 patients included: 33 cases and 33 matched controls. Dronabinol was initiated 55 (28–107) hours from admission. Cases and controls were well matched. Cases had a significant reduction in opioid consumption with adjunctive dronabinol (−79 (20) MME, p<0.001), while opioid consumption was unchanged for controls (−9 (20) MME, p=0.63). This resulted in a ninefold greater reduction in opioid consumption for cases versus controls that was statistically different between pairs (p=0.02). Nineteen (58%) cases reported using marijuana; in this subset, opioid consumption was reduced with adjunctive dronabinol (−97 (24) MME, p<0.001) versus a non-significant increase in opioid consumption in matched controls (11 (29) MME, p=0.70); difference between groups, p=0.01. Conclusions: The results of this study suggest adjunctive dronabinol reduces opioid consumption following traumatic injury. The opioid-sparing effect of dronabinol may be greater in patients who are marijuana users. Level of evidence: III.